ADOPSI E-COMMERCE PADA UMKM DI KOTA SUBANG MENGGUNAKAN MODEL UTAUT - Rian Piarna; Tri Herdiawan Apandi (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
One of the growing business activities in Indonesia is Small and Medium Enterprises (SMEs). MSMEs have an important and strategic role in national economic development. However, the use of technology in SMEs activities is still not optimal. SMEs business players still encounter obstacles that still exist, namely, difficulties in the process of monitoring transaction payments, the cost of internet access which is still relatively expensive and more time and effort to understand e-business technology for business people. This study aims to analyze the relationship between factors that influence the adoption of e-commerce by SMEs in the city of Subang by using the Unified Theory of Acceptance and Use of Technology (UTAUT) model approach. UTAUT is a model to describe the factors that influence intention to use internet technology (e-commerce). The sample in this study were 165 SMEs. Data processing using SMART PLS. The results show that the Effect of PE (Performance Expectancy) on BI (Behavioral Intentions), SI (Social Influence) on BI, BI on USE (Use Behavior) and FC (Facilitating Conditions) on UB is significant. Keyword: e-commerce, Smart PLS, SMEs, Subang, UTAUT